Two independent families with de novo whole APC gene deletion and intellectual disability: a case report - Moriya Iwaizumi; Terumi Taniguchi; Risa Kojima; Harumo Osawa; Kyota Tatsuta; Mayu Sakata; Satoshi Osawa; Kiyotaka Kurachi; Ken Sugimoto (Hereditary Cancer in Clinical Practice)
Abstract Background Familial adenomatous polyposis (FAP) is an autosomal dominant colorectal tumour syndrome characterised by the formation of multiple adenomatous polyps throughout the colon. It is important to understand the extracolonic phenotype that characterizes FAP. Most previous case reports of patients with both FAP and intellectual disability (ID) have described deletions in all or part of chromosome 5q, including the APC locus. However, it remains unclear whether the ID phenotype in patients with FAP is due to APC disruption or another genetic defect in the deleted 5q region. Case presentation Patient of family 1 is a 32-year-old woman presented with > 500 colorectal adenomatous polyps, gastric fundic gland polyposis, several duodenal adenomas, and mild intellectual disability (ID). She had no known family history of the FAP phenotype or ID. By copy number trio analysis, a 15.4 Mb interstitial heterozygous de novo deletion including APC region was observed in 5q21.2. q22.3. The patient in family 2 was a 29-year-old man with approximately 50 colorectal adenomatous polyps, fundic gland polyposis in the stomach, non-ampullary adenomas in the duodenum, and mild ID. He had no family history of the FAP phenotype or ID. Using copy number trio analysis, a de novo 9.8 Mb heterozygous deletion was identified on 5q22.1. q23.1 which includes the APC region. Conclusions Based on previous reports and the present study, we narrowed down the 5p deletion region associated with ID in FAP. Further investigation is required to understand ID due to 5q stromal deletion.